Abnormal morphology and function in retinal ganglion cells derived from patients-specific iPSCs generated from individuals with Leber's hereditary optic neuropathy. Issue 2 (10th August 2022) - Nie, Zhipeng; Wang, Chenghui; Chen, Jiarong; Ji, Yanchun; Zhang, Hongxing; Zhao, Fuxin; Zhou, Xiangtian; Guan, Min-Xin
Abstract: Leber's hereditary optic neuropathy (LHON) is a maternally inherited eye disease that results from degeneration of retinal ganglion cells (RGC). Mitochondrial ND4 11778G > A mutation, which affects structural components of complex I, is the most prevalent LHON-associated mitochondrial DNA (mtDNA) mutation worldwide. The m.11778G > A mutation is the primary contributor underlying the development of LHON and X-linked PRICKLE3 allele (c.157C > T, p.Arg53Trp) linked to biogenesis of ATPase interacts with m.11778G > A mutation to cause LHON. However, the lack of appropriate cell and animal models of LHON has been significant obstacles for deep elucidation of disease pathophysiology, specifically the tissue-specific effects. Using RGC-like cells differentiated from induced pluripotent stem cells (iPSCs) from members of one Chinese family (asymptomatic subjects carrying only m.11778G > A mutation or PRICKLE3 p.Arg53Trp mutation, symptomatic individuals bearing both m.11778G > A and PRICKLE3 p.Arg53Trp mutations and control lacking these mutations), we demonstrated the deleterious effects of mitochondrial dysfunctions on the morphology and functions of RGCs. Notably, iPSCs bearing only m.11778G > A or p.Arg53Trp mutation exhibited mild defects in differentiation to RGC-like cells. The RGC-like cells carrying only m.11778G > A or p.Arg53Trp mutation displayed mild defects in RGC morphology, including the area of soma and numbers of neurites, electrophysiological properties, ATP contents and apoptosis. Strikingly, those RGC-like cells derived from symptomatic individuals harboring both m.11778G > A and p.Arg53Trp mutations displayed greater defects in the development, morphology and functions than those in cells bearing single mutation. These findings provide new insights into pathophysiology of LHON arising from RGC deficiencies caused by synergy between m.11778G > A and PRICKLE3 p.Arg53Trp mutation. Graphical abstract: